Morphology, ultrastructure and life cycle of Vitrella brassicaformis n. sp., n. gen., a novel chromerid from the Great Barrier Reef - Oborník, Miroslav; Modrý, David; Lukeš, Martin; Cernotíková-Stříbrná, Eva; Cihlář, Jaromír; Tesařová, Martina; Kotabová, Eva; Vancová, Marie; Prášil, Ondřej; Lukeš, Julius (Protist, 2012)
Chromerida are photoautotrophic alveolates so far only isolated from corals in Australia. It has been shown that these secondary plastid-containing algae are closely related to apicomplexan parasites and share various morphological and molecular characters with both Apicomplexa and Dinophyta. So far, the only known representative of the phylum was Chromera velia. Here we provide a formal description of another chromerid, Vitrella brassicaformis gen. et sp. nov., complemented with a detailed study on its ultrastructure, allowing insight into its life cycle. The novel alga differs significantly from the related chromerid C. velia in life cycle, morphology as well as the plastid genome. Analysis of photosynthetic pigments on the other hand demonstrate that both chromerids lack chlorophyll c, the hallmark of phototrophic chromalveolates. Based on the relatively high divergence between C. velia and V. brassicaformis, we propose their classification into distinct families Chromeraceae and Vitrellaceae. Moreover, we predict a hidden and unexplored diversity of the chromerid algae.
Keywords: spory protozoální; biologické pigmenty; xanthofyly; Coral Reefs; fylogeneze; chlorofyl a; Flagella; Phylogeny; Chlorophyll; genom plastidový; Chlorophyll A; flagella; elektronová mikroskopie; Genome, Plastid; chlorofyl; Cell Membrane; Spores, Protozoan; beta-karoten; beta Carotene; buněčná stěna; Cell Wall; Plastids; Microscopy, Electron; buněčná membrána; plastidy; Alveolata; Pigments, Biological; Xanthophylls; korálové útesy